Progesterone Levels and Estrus Symptoms in Modified Ovsynch Protocols in Khillar Cows - Barde, Mayank Diwakar; Ingawale, Maheshkumar Vitthalarao; Deshmukh, Shyam Ganesh; Pawshe, Chaitanya Hemednrakumar; Ingole, Ranjit Suresh; Awandkar, Sudhakar Prahlad (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The progesterone levels and estrus signs were studied in Ovsynch, double PG Ovsynch and increasing dose of PG in Ovsynch synchronization protocols in multiparous lactating Khillar cows (6 each) under field conditions. The tumefaction of vulval lips and cervical mucus discharge were most prominent estrus behaviour signs exhibited by 88 % cows in all the three groups. The mean serum progesterone levels on the day of estrus were 0.95 ± 0.77, 0.82 ± 0.04 and 0.90 ± 0.03 ng/mL in Ovsynch, double PG Ovsynch and increasing dose of PG in Ovsynch protocols, respectively, which did not differ statistically. The pregnancy rate observed was also non significantly higher in double PG Ovsynch synchronized cows than other two groups (50% vs 33.33%). The serum progesterone during estrus in double PG Ovsynch synchronization protocol was lower indicating better estrus quality with recorded higher pregnancy rate than Ovsynch and increasing dose PG protocol.